Brain tumour? – Cerebellar histoplasmosis as a solitary mass lesion. (October 2019) - Riste, Michael; Bodasing, Neena; Cadwgan, Anthony
A 50-year-old man who had been living in Thailand presented with a history of falls, deteriorating vision and weight loss over several months. He had been admitted to a hospital in Thailand where he was given a diagnosis of multiple sclerosis. Neurological examination revealed a mild ataxic gait and lateral nystagmus, but no other abnormalities. He tested positive for human immunodeficiency virus with a CD4 cell count of 16 cells/µL. Brain magnetic resonance imaging was suggestive of an intrinsic neoplasm and he underwent stereotactic brain biopsy which showed numerous yeast-like organisms. Panfungal polymerase chain reaction was positive for Histoplasma capsulatum . He received liposomal amphotericin B for six weeks, followed by itraconazole, and started antiretroviral therapy four weeks into treatment. He developed an immune reconstitution inflammatory syndrome which responded well to steroids. Six months after diagnosis, he has no neurological symptoms or signs and remains on itraconazole. Isolated bulky central nervous system histoplasmomas are exceedingly rare. A clinical suspicion of immunosuppression was key in making this diagnosis.